Prince she shouldn't crave - Anthony, Kali (Harlequin presents, 2025)
"An off-limits temptation... fit for a royal! Though Crown Prince Gabriel Montroy hates the media, he was raised to always put his kingdom first. When his political opponents rile up the tabloids, he reluctantly hires PR consultant Lena Rosetti. He just wasn't prepared for Lena's effervescent warmth to threaten his icy control... Both their reputations rest on Lena's success, yet she can barely think straight around His Highness. Especially once she discovers dutiful Gabriel is entertaining the same forbidden thoughts as her... But if the paparazzi sniff out their red-hot spark, it will create a scandal even Lena can't fix!" --